The recovery of homicidal people diagnosed with schizophrenia and schizoaffective disorder—An interpretative phenomenological analysis - Kovács, Asztrik; Ladányi, Bence; Farkas, Noémi; Stempel, Laura; Kiss, Dániel; Bittermann, Évi; Rácz, József (Frontiers in Psychiatry, 2023)
Objective: Identity recovery for people diagnosed with schizophrenia who committed homicide raises several difficulties. Premorbid mental illnesses, the experience of psychosis and the lack of cohesive ego functions might result in the inability to integrate the homicidal act into self-identity. Problems with integration risk recidivism and further mental problems. This research aimed to explore how homicidal people diagnosed with schizophrenia make sense of their act and how do they identify with the homicide. Method: Six semi-structured interviews were made with people who have committed a homicide and diagnosed with schizophrenia at a long-term psychiatric home. Interviews were transcribed verbatim and analyzed with Interpretative Phenomenological Analysis. IPA is an idiographic method rooted in phenomenologist traditions. It is focusing on how participants experience and make sense of events in their lives, and how it affects their identities and sense of self. Results: Three Personal Experimental Themes were established as a result of the analysis: 1. Homicide and responsibility, 2. Homicide and self, 3. Control over threatening self and self evaluation 1. Homicide was often reported to have been committed in a non-conscious, delusional state and might lead to the loss of self-determination. 2. Our interviewees struggled to integrate their act into their identities. They were found to alienate the crime from themselves or to have multiple, parallelly existing interpretations of the act. 3. Recovering patients are experiencing a constant threat of getting into the delusional reality and losing control. The importance of control became central in self-evaluation. Conclusion: Therapy aiming at self-control, supporting the integration of fragmented self and raising awareness on the connections of delusional and standard reality is might be helpful for reducing the instability of self. Therapy aiming to process the complicated grief and loss of family is needed.